Developmental assessment and performance analysis of vertical jump in schoolchildren. DOI: http://dx.doi.org/10.5007/1980-0037.2012v14n4p460 - Dalker Roberto Walter; Pedro Paulo Depra (Universidade Federal de Santa Catarina, 2012)
DOI: http://dx.doi.org/10.5007/1980-0037.2012v14n4p460The vertical jump involves different levels of skill complexity and offers the individual a wide range of motor experiences. This study aimed to determine which movements in the developmental sequence performed by schoolchildren are associated with age and vertical jump performance. The sample consisted of 137 elementary school children of both sexes, aged 7-10y, with height of 1.19-1.63 m, and weight of 20-60 kg. All children were selected from first- to fourth-grade classrooms of a public school of the city of Maringá, state of Pa- raná, Brazil. A Gallahue & Ozmun matrix and a jumping platform were used as research instruments. During the experiment, each child performed three jumps. Simultaneous and coordinated upward arm lift was observed in 7-year-old children. In 9-year-old children, inconsistent preparatory crouch and lack of coordination between limb movements and trunk were observed. A prevalence of upper limb motor acts was observed when considering the significant associations found between elements of the developmental sequence and vertical jump performance. In children aged 7-10y, age group and jumping performance are associated with elements of the developmental sequence of the human body as a whole, especially with regard to the upper limbs.